Fragility analysis of masonry wall subjected to blast loading. (May 2022) - Shamim, Saba; Ahmad Khan, Rehan; Ahmad, Shakeel
Abstract: The present research focuses on developing the Fragility Curves (FC) of masonry panels subjected to various blast scenarios considering extensive parameters such as the effect of variation in types of masonry (unreinforced and reinforced) and blast explosion (air and surface). The Fragility Curve (FC) is a suitable way of illustrating the vulnerability of structure against blast load. Herein; fragility analysis of Solid Brick Masonry (SBM), Hollow Brick Masonry (HBM) and Reinforced Hollow Brick Masonry (RHBM) wall panels were carried out to assess their vulnerability against blast load using explicit finite element approach. The FC(s) were plotted considering uncertainties in blast parameters viz., weight of charge (W) and standoff distance (R). Two types of FC(s) were plotted: FC-1, with Probability of Failure (PF) as ordinate and W as abscissa; and FC-2, with PF on ordinate-axis and scaled distance Z [f (W, R)] on abscissa. Monte Carlo simulation (MCS) was adopted to generate random sample sets of variables based on the mean value and coefficient of variation. The failure criterion assumed in this study is based on the inelastic tension damage curve generated for the masonry in accordance with the experimental results. Also, a Damage Index was established having four levels of damage- Minor Damage (MD), Repairable Damage (RD), Non-Repairable Damage (NRD) and Total Damage (TD). In addition, limit state function was defined in terms of cracking strain for which the threshold values corresponding to each damage level was specified on the basis of tension damage curve. The various critical values of W and Z corresponding to the probability of TD being 90% were reported from the FC(s). It was found that percentage increase in demand of W critical for RHBM was about 100%–400% approximately for various standoff distances between 5 m and 40 m. Also, due to strengthening value of Z critical decreased to 21% and 27.5% respectively for surface and air blast scenario respectively.